2017
DOI: 10.3138/cmlr.2016-0010
|View full text |Cite
|
Sign up to set email alerts
|

Non-Native Speakers of the Language of Instruction: Self-Perceptions of Teaching Ability

Abstract: Given the linguistically diverse instructor and student populations at Canadian universities, mutually comprehensible oral language may not be a given. Indeed, both instructors who are non-native speakers of the language of instruction (NNSLIs) and students have acknowledged oral communication challenges. Little is known, though, about how the NNSLI population perceives its ability to teach in a second language (L2). This paper presents results pertaining to one part of a larger, exploratory study that investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For example, from the perspective of the general law of teaching activities, Zhou Yuanyuan thinks that the structural teaching ability of teachers includes the ability to organize and monitor teaching, the ability to communicate with teachers or other students, the ability to use modern technology and information, and the ability to conduct teaching research and lifelong learning. Tian Jinmei et al constructed a conceptual model of teachers' teaching ability, including teaching ability, knowledge promotion ability, training ability, and method and tool application ability [21], by studying the current situation of teachers' teaching ability at home and abroad and combining with many factors such as teachers' living environment.…”
Section: Evaluation Of Teaching Quality In Colleges Andmentioning
confidence: 99%
“…For example, from the perspective of the general law of teaching activities, Zhou Yuanyuan thinks that the structural teaching ability of teachers includes the ability to organize and monitor teaching, the ability to communicate with teachers or other students, the ability to use modern technology and information, and the ability to conduct teaching research and lifelong learning. Tian Jinmei et al constructed a conceptual model of teachers' teaching ability, including teaching ability, knowledge promotion ability, training ability, and method and tool application ability [21], by studying the current situation of teachers' teaching ability at home and abroad and combining with many factors such as teachers' living environment.…”
Section: Evaluation Of Teaching Quality In Colleges Andmentioning
confidence: 99%
“…There are no statistical differences at α≥0.05 in the students' achievement due to gender. Ismaiel (2017) revealed results that disagree with this result but some other studies such as (Lin & Lu, 2016;Samuel, 2017;Üstünlüoglu, 2007) agree with theis result. That they consider gender is not an effective factor to show the impact of NNESTs AND nests.…”
Section: Discussionmentioning
confidence: 60%
“…However, in spite of the existence of successful research experiences on NSs and NNSs cooperation, such as De Oliveira and Richardson (2001), they are still very difficult to find in the literature. Samuel (2017) argues that the native speaker norm results in dividing the English language teaching profession according to a class system and that it should be eliminated. Kachru and Nelson (1996) Being a monolingual speaker of a language (which is rare) and being born in a particular place does not adequately facilitate the quest in defining the native speaker since many native speakers of a language do, in fact, speak other languages besides their own; and monolinguals may be the exception rather than the norm (Ling & Braine, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the participants had developed a critical perspective on the native/nonnative teacher divide, they were influenced by nativespeaker models when it came to proficiency in English. Samuel (2017) found that the NNESTs in his study spent more time on lesson preparation because they teach in their L2. These teachers also made decisions on classroom instructional practice in line with their self-perceptions of teaching ability.…”
Section: Introductionmentioning
confidence: 81%